1997
DOI: 10.1021/ic961389n
|View full text |Cite
|
Sign up to set email alerts
|

Absorption, Fluorescence, and Magnetic Circular Dichroism Spectra of and Molecular Orbital Calculations on Tetrabenzotriazaporphyrins and Tetranaphthotriazaporphyrins

Abstract: Extensive analyses of the electronic absorption, magnetic circular dichroism (MCD), and fluorescence emission and excitation spectra of peripherally-substituted tetrabenzotriazaporphyrin (TBTrAP) and tetranaphthotriazaporphyrin (TNTrAP) complexes are reported. ZINDO calculations of the UV−visible absorption spectra of free base and dianionic (deprotonated) TBTrAP and TNTrAP complexes are described. The optical spectra of TBTrAP and TNTrAP are assigned on the basis of molecular orbital (MO) calculations using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 82 publications
2
17
0
Order By: Relevance
“…The intensity of the Faraday B terms of the Q band decreases in the order TAP>TAC>TAB, and this reflects the degree of splitting of the Q band 23–25. The sign pattern of the MCD B term bands of all compounds is −/+ with increasing energy, as is also seen for low‐symmetry Pc derivatives,26–30 although those of hydrogenated porphyrins were often inverted 21, 31…”
Section: Resultsmentioning
confidence: 69%
“…The intensity of the Faraday B terms of the Q band decreases in the order TAP>TAC>TAB, and this reflects the degree of splitting of the Q band 23–25. The sign pattern of the MCD B term bands of all compounds is −/+ with increasing energy, as is also seen for low‐symmetry Pc derivatives,26–30 although those of hydrogenated porphyrins were often inverted 21, 31…”
Section: Resultsmentioning
confidence: 69%
“…1 and Table 1), as expected for a macrocycle with lower symmetry than that of the Pc ring. Mack et al [30] have calculated the electronic energy levels for TBTAP molecules; a splitting in the lowest unoccupied molecular orbital (LUMO) leads to split Q-and B-bands [30].…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…These include two phthalocyanine derivatives, (Cl) 2 SnPc(C 6 H 13 ) 8 (3a) and (Cl) 2 SnPc(C 10 H 21 ) 8 (3c), and the corresponding dichlorotin octaalkyl-tetrabenzotriazaporphyrin, (Cl) 2 Sn(IV)TBTAP (3b), an example of a rarer class of macrocycle but one closely related to the phthalocyanines [30]. …”
Section: Introductionmentioning
confidence: 99%
“…The synthetic chemistry of these ring compounds has flourished, with a great many compounds being reported that exhibit properties at the extremes of the 'normal' range. To some extent, synthetic development has been greater recently with the tetraaza-, triaza-and subphthalocyanine cores than with the porphyrin core-see as an example the detailed review of synthetic and spectroscopic characterization of the subphthalocyanines by Kobayashi [20] and the spectroscopic properties and molecular orbital calculations for the triazaporphyrins [21]. Recently, also, there has been an increase in the synthesis and characterization of linked porphyrins and phthalocyanines, e.g.…”
mentioning
confidence: 99%